ARAHAN PENGGUNAAN LAHAN BERDASARKAN PERHITUNGAN CURAH HUJAN DAN FLUKTUASI DEBIT AIR PADA DAS WAE BATU GAJAH KOTA AMBON DALAM KURUN WAKTU EMPAT TAHUN (2010-2013) - Erbabley, Baltazar Zadrak (Hibualamo : Seri Ilmu-Ilmu Alam dan Kesehatan, 2017)
Watershed is an area of land which is a unity with the river and its tributaries. The function are collecting, storing and draining water. Land requirements influence the poor condition of Wae Batu Gajah watershed for urgent and reducing the vegetated lands. This study aims to formulate land use appropriate referrals based on the calculation of the amount of rainfall and water discharge fluctuations Wae Batu Gajah watershed during a period of four years (2010-2013). The research method using digitized on screen to answer the first goal, a simple linear regression analysis to answer the second goal. The guideline for the land use in Wae Batu Gajah watershed based on calculation rainfall and water flow fluctuations that are tailored to the characteristics of Wae Batu Gajah watershed Ambon used a Government Regulation Number 44 in 2004 concerning Forestry Planning. Data collected in the form of primary data from field surveys, and secondary data from relevant agencies that support this research. Based on calculations using simple linear regression, ties between rainfall (X) of the water discharge (Y) in 2010, 2011, 2012 and 2013 found the equation Y = 0.320917839 + 0.250668724 X with a correlation coefficient (r) = 0.679 and the coefficient determination (R?) = 0.461 which means 46.10 percent change in water flow in 2010-2013 was influenced by rainfall.